2009
DOI: 10.1021/nl8036245
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of Metal−Carbon Nanotube Interfaces for Regrowth and Electronic Transport

Abstract: First principles and tight binding Monte Carlo simulations show that junctions between single-walled carbon nanotubes (SWNTs) and nickel clusters are on the cluster surface, and not at subsurface sites, irrespective of the nanotube chirality, temperature, and whether the docking is gentle or forced. Gentle docking helps to preserve the pristine structure of the SWNT at the metal interface, whereas forced docking may partially dissolve the SWNT in the cluster. This is important for SWNT-based electronics and SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 33 publications
7
46
0
Order By: Relevance
“…These SWNTs are longer than the TB cutoff distance, and the similarity between the results obtained from these SWNTs and those obtained from shorter capped SWNTs [14] supports the fact that the use of long or capped SWNTs does not affect the data presented here. The calculations were performed at 1000 or 1500 K, which is relevant to chemical vapor deposition growth and regrowth of SWNTs.…”
Section: Methodssupporting
confidence: 85%
See 4 more Smart Citations
“…These SWNTs are longer than the TB cutoff distance, and the similarity between the results obtained from these SWNTs and those obtained from shorter capped SWNTs [14] supports the fact that the use of long or capped SWNTs does not affect the data presented here. The calculations were performed at 1000 or 1500 K, which is relevant to chemical vapor deposition growth and regrowth of SWNTs.…”
Section: Methodssupporting
confidence: 85%
“…Their study showed that solubility of carbon atoms in nickel is limited, but that carbon atoms are also stable at subsurface sites. The validity of the Hamiltonian for studying SWNT-Ni cluster systems has been conÀrmed by comparison with DFT calculations [14]. À Nano Res (2009) 2: 774 782…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations